PENGARUH PROFITABILITAS, AKTIVA TIDAK BERWUJUD, UKURAN PERUSAHAAN, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Kemara Dewi, Anak Agung Ayu; Badjra, Ida Bagus (E-Jurnal Manajemen, 2017)
The company's goal is to maximize profits. The development of the theory of the company to change their views about the company's goal becomes maximizing wealth . Increasing the value of the company would require the role of managers in decision-making achievement of company objectives. Managers need to consider the factors that affect the value of the company in the interests of stakeholders. This study aims to determine the effect of profitability, company size, intangible assets, and capital structure partially to the company's value. The study sample consisted of 10 pharmaceutical companies in the IDX. The analysis technique used multiple linear regression analysis. The results showed that profitability, and intangible assets significant positive effect on firm value. Company size is not significant positive effect on corporate value and capital structure significant negative effect on firm value.
Keywords: firm value; profitability; intangible assets; company size; capital structure